Al Saj’u fī Sūrati al Jinni (Dirāsatun fī ‘ilmi al Badī’i) - Wahyuni, Rahmi Fitri; Yusuf, Muhammad (Al-Uslub: Journal of Arabic Linguistic and Literature, 2020)
The purpose of this research is: 1) To know the kinds of sajak contained in surah Al-Jinn 2) To know the specificity of the sajak contained in surah Al-Jinn. The type of research used is Pustaka Study. It can be inferred from the results of this study:1) The sajak contained in Surah Al-Jinn there are two kinds namely Sajak Mutarraf and sajak mutawazzi، of which mutarraf has as many as 8 fashilah and Sajak Mutawazzi as many as 7 fashilah. 2) The Specificity of The Sajak in Surah Al-Jinn; 1) Provide its own secrets in its beauty and tone. 2) Provide similarities between 1 faqroh and faqroh faqroh which differ in terms of length. 3) Distinguished by absence in word repetition، abstaining from boredom for the reader 4) Fostering an idea that can be set in a thought for repetition used in each of them